A Cross-Cultural Adaptation of the Czech Version of the Developmental Coordination Disorder Questionnaire: The Content Validity Part - Vlasakova, Nikol; Musalek, Martin; Cepicka, Ladislav (Children, 2024)
The Developmental Coordination Disorder Questionnaire (DCDQ) is a widely used parent questionnaire for screening motor coordination disorders in children aged 5-15 years. Despite increasing motor difficulties in children, a validated version is lacking in Central Europe. In addition, previous studies pointed out that several DCDQ items were shown to be problematic in different cultural environments. We found that the majority of these studies did not assess the item's content validity approach for keeping the semantic form and linguistic intelligibility of the original items. Therefore, this study aimed to translate the DCDQ, determine the content validity of items, and adapt the DCDQ for Czech children aged 6-10 years, where the identification of motor difficulties is crucial. Back-translation was employed, and face validity was consulted with linguistic experts and occupational therapists. A sample of 25 bilingual parents and practitioners evaluated the translated version, with content validity assessed using the Content Validity Ratio coefficient (CVR). Initial CVR scores ranged from 0.6 to 1.0. Lower scores were found for items 14 and 15, which were shown to be problematic in previous studies. The reason for the lower content validity in these items was due to double negation. Following linguistic modifications, the CVR values improved (range: 0.87-1.0), indicating content and semantic stability. Our findings underscore the importance of considering content validity and language specificity, including issues like double negation, during cross-cultural questionnaire validation to mitigate potential psychometric concerns in the future. The adapted Czech version exhibits significant content validity, thereby warranting further validation of its psychometric properties.